(untitled) (Annals of Bangladesh Agriculture, 2025)
The identification of stable maintainer and restorer lines strengthens sustainable hybrid rice technology to increase its production and support the self-sufficiency of food in Bangladesh. Experiments were conducted to assess the genetic variation among 47 prospective maintainer and restorer lines selected from coastal rice collections in the Genetics and Plant Breeding experimental field and laboratory of Gazipur Agricultural University, Gazipur during 2021-2023. Most of the Agronomic and floral traits were significantly (P<0.001) varied. The phenotypic coefficient of variation - was very close to the genotypic coefficient of variation - for almost half of the studied traits, indicating a moderate influence of the environment. High heritability (h2b) combined with high genetic advance as percent of mean (GAM %) suggests the presence of additive gene effects that influence the traits observed. Principal Component Analysis - and a scree plot showed that the first six components of the traits accounted for 83.29% of the total variation. Grain yield/hill (g) was significantly positively correlated with flowering, maturity, and panicle-related traits, including 1000-grain weight, gain length, and grain breadth, as observed through correlation and biplot analyses, but a negative relationship was also exhibited with some traits. The UPGMA dendrogram grouped the genotypes into six clusters, where L003 and L083 each occupied a single cluster. Based on agronomic and floral traits, the prospective maintainers viz.L006, L013, L019, L025, L038, - and restorers viz. L001, L004, L015, L033, L037, L038, L058, L062, L065, L067, L099 seemed to hold significant potential for future breeding programs for the development of hybrid rice adaptive to coastal regions of Bangladesh. Ann. Bangladesh Agric. 28(2): 1-23